SUBJECTS OF INNOVATIVE ACTIVITY: ANALYSIS OF CLASSIFICATION BASED UPON THE EXTENT OF KNOWLEDGE USE - L. V. Obolenskaya; M. M. Kandokhova (Финансы: теория и практика, 2017)
To date, the distinguishing characteristic of the economic structure of industrialized countries is the fact that services, knowledge and information play a significant role and replace the traditional production of material goods. The increased role of services in knowledge-intensive areas makes it necessary to monitor and evaluate the ongoing structural shifts and introduce into practice an appropriate classification system.The first part of the article analyzes the foreign experience in classification of subjects of innovative activity, namely, the classification based upon the extent of knowledge use. Two methodologically similar classifications used abroad to monitor the manufacturing and service sectors are considered. The main feature of these classifications is the allocation of subjects of innovative activity into different aggregated blocks according to the extent of knowledge use. The first of the two classifications came into use in Russia. The idea to extend the approach used in the manufacturing industry to the service sector looks like a promising one.The second part evaluates the importance of the service sector by analyzing the experience of some EU countries where the services represent a major element of high tech activities. The assessment is made by comparing the high-tech service sector and manufacturing sector.Comparison is made through a series of calculated indicators that reflect the scale of production, the added value and the added value share in the production volume. The two sectors which are key factors in the development of entrepreneurial activity — small and medium high-tech businesses — are compared using indirect assessments. For all analyzed parameters, the service sector points higher than manufacturing sector.